Anterior-posterior and inter-limb lower body strength asymmetry in soccer, basketball, futsal, and volleyball players - Parpa, K.; Michaelides, M. (Medicina, 2022)
Background and Objectives: The purpose of this study was twofold: (1) to examine strength asymmetries in elite athletes of different sports and (2) to examine the magnitude of asymmetries between elite and u18 athletes.